Beyond Alienation: Reason Why Street-Level Bureaucrats Chose Discretion to Implement a Policy (A Case Study of Maybrat's Prospective Civil Servants' Training) - Mifrohatun Fathiyah, Anisa (Indonesian Association for Public Administration (IAPA), 2024)
Discretion and street-level bureaucrats (SLB) are inseparable. SLB are seen to have better understanding and closer to what really happened in society, thus made SLB chose discretion so the implementation of a public policy can work successfully. Alienation, known as the condition where a policy is disconnected to its implementor, was said to be one of the main factors why SLB use discretion in implementing a policy outside what's been written. The previous researches had proven the connection between alienation and SLB's discretion decision, but what happened to the discretion that The Center for Training and Development and Government Management Research (Puslatbang KMP) chose to implement the blended learning policy for the prospective civil servants' training in Maybrat proved differently. Four out of five dimensions of alienation did not happen when Puslatbang KMP implemented the policy, yet discretion was still implemented for the prospective civil servants in Maybrat. The lack of training infrastructures, the low level of training participants' ability to access digital training platform, and the ever-changing security risks created what called needed deservingness for Maybrat's civil servants and made Puslatbang KMP chose discretion in implementing blended learning policy for them.